Results in development : report 2007-2008 (The Ministry The HagueNL, 2009)
Presents the results of Dutch development cooperation. Discusses the progress made in achieving the Millennium Development Goals, the Netherlands' contribution and what forms that contribution took. Supplements the Ministry of Foreign Affairs' annual report on the progress of Dutch development cooperation.
Keywords: DEVELOPMENT AID